Corporate Social Responsibility: Does One Size Fit All - CHOUDHARY, ANAND (IJRDO - Journal of Business Management, 2018)
As multinational corporations (MNCs) increasingly shift base to developing countries they are also required to manage different demands from various stakeholder groups in those countries which often creates a dilemma in front of the managers on whether to follow the corporate social responsibility (CSR) policies of their home-country or to tailor it according to the demands and expectations of local stakeholder groups including local communities in regions where the MNC operates. The current article examines how the managers of the MNCs operating in developing countries may manage the different needs and expectations of various stakeholder groups whilst advocating that one size fits all approach for CSR does not work. The results indicate that today it’s increasingly being expected by communities and policymakers that the large profit making MNCs should also contribute towards reducing poverty especially in developing countries and it is in businesses’ long-term interest to contribute towards building human capital in developing economies where they operate as it will result in potentially millions of more customers for their products and services whilst improving the corporate or the brand image of the company in the eyes of the stakeholders and thus creating a win-win situation for all.